2018
DOI: 10.22146/ijc.21175
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Ni-Zn LHS and Mg-Al LDH Adsorbents of Navy Blue and Yellow F3G Dye

Abstract: Adsorption of disperse dyes from wastewater onto Ni-Zn LHS (layered hydroxide salts) and Mg-Al LDH (layered double hydroxides) has been compared in this study. Effects of initial pH solution, contact time and initial dye concentration were investigated. The ability of the adsorbent to be reused was also studied. The results showed that acidic condition was favorable for the adsorption of each dyes onto both adsorbent. The adsorption kinetics was studied using pseudo-first-order, pseudo-second-order and Santosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The appearance of hydrogen bond related to hydroxyl layers in the nanoparticles of co-coated Mg/Al-LDH confirmed the formation of a bond between LDH and FPEG-drug nanoparticles. For example, the asymmetric and symmetric stretching mode of O-H group in Mg/Al–OH of Mg/Al–LDH at 3416 cm −1 was shifted to 3398 cm −1 76. The band at 1636 cm −1 is due to the bending vibration (H–O–H) of interlayer water molecules was shifted to 1622 cm −1 .…”
Section: Resultsmentioning
confidence: 94%
“…The appearance of hydrogen bond related to hydroxyl layers in the nanoparticles of co-coated Mg/Al-LDH confirmed the formation of a bond between LDH and FPEG-drug nanoparticles. For example, the asymmetric and symmetric stretching mode of O-H group in Mg/Al–OH of Mg/Al–LDH at 3416 cm −1 was shifted to 3398 cm −1 76. The band at 1636 cm −1 is due to the bending vibration (H–O–H) of interlayer water molecules was shifted to 1622 cm −1 .…”
Section: Resultsmentioning
confidence: 94%
“…This confirmed the presence of PVA in the magnetite core-shell nanoparticles. For the MLDH FTIR spectrum (Figure 3D), the O–H bending vibration band was observed at 3416 cm −1 [36,37]. It can be observed that this band was shifted to 3398 cm −1 due to the formation of a bond between LDH and FPVA–drug nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The second weight loss was representative of the loss of the chain of the iron atom [44]. The major decomposition at 282 °C that corresponds to 7.7% weight loss is due to the thermal decomposition of nitrate ions of the MLDH nanocarrier [36]. The weight loss between 500–800 °C involved the removal of interlayer anion decomposition and the collapse of the layered structure.…”
Section: Resultsmentioning
confidence: 99%
“…To decrease the environment pollutant in water containing dyes, there are some attempt such as electro-decolorization process (Amal, Febiyanto, Soleh, & Afif, 2016;Khosravi, Fazlzadehdavil, Barikbin, & Hossini, 2015), photocatalysis reaction (Febiyanto, Eliani, Riapanitra, & Sulaeman, 2016;Febiyanto et al, 2019), adsorption (Ikhsani, Santosa, & Rusdiarso, 2016;Subramani & Thinakaran, 2017), separation…”
Section: Introductionmentioning
confidence: 99%